2020
DOI: 10.1038/s41438-020-0295-3
|View full text |Cite
|
Sign up to set email alerts
|

A high-quality reference genome of wild Cannabis sativa

Abstract: Cannabis sativa is a well-known plant species that has great economic and ecological significance. An incomplete genome of cloned C. sativa was obtained by using SOAPdenovo software in 2011. To further explore the utilization of this plant resource, we generated an updated draft genome sequence for wild-type varieties of C. sativa in China using PacBio single-molecule sequencing and Hi-C technology. Our assembled genome is approximately 808 Mb, with scaffold and contig N50 sizes of 83.00 Mb and 513.57 kb, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 56 publications
3
62
0
1
Order By: Relevance
“…Recently, hemp phytochemical pathway genes have been extensively studied via omics approaches ( Braich et al, 2019 ; Vincent et al, 2019 ; Gao et al, 2020 ). However, the characterization of function on most of phytochemical pathway genes remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, hemp phytochemical pathway genes have been extensively studied via omics approaches ( Braich et al, 2019 ; Vincent et al, 2019 ; Gao et al, 2020 ). However, the characterization of function on most of phytochemical pathway genes remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the first draft Cannabis reference genome, and transcriptome, were constructed in 2011 using the high THCA, low CBDA cultivar, 'Purple Kush', and the high CBDA, low THCA hemp strains, 'Finola' and 'USO-31' [363]. Using a PacBio long-read sequencing platform, the Purple Kush and Finola genomes were again sequenced in 2019 to generate a physical and genetic map for Cannabis, and further distinguish the genes, and importantly the gene products (specifically, the encoded enzymes), underpinning the secondary metabolite profiles responsible for the divergent chemotype between hemp and marijuana cultivars [364,365].…”
Section: Next-generation Sequencing Of the Cannabis Plant And Its Potmentioning
confidence: 99%
“…This could help in the production of medical/recreational cannabis without the risk of mildew contaminants that could be dangerous for consumers. In parallel, Gao et al (2020) assembled a new genome of C. sativa deriving from wild samples collected in Tibet using a combination of PacBio and Hi-C technologies. Despite all these efforts, an exhaustive meta-analysis of all the cannabis genomics data published so far ( Kovalchuk et al, 2020 ) demonstrated that the currently available cannabis genome assemblies are: i) incomplete, with approximately 10% missing, 10–25% unmapped, and centromeres and satellite sequences unrepresented; ii) ordered at a low resolution and only partially annotated for what concerns genes, partial genes, and pseudogenes.…”
Section: Advances In Cannabis Genomicsmentioning
confidence: 99%